Retour au terrain ! - Bernard Davasse; Dominique Henry; Jean-François Rodriguez (Projets de Paysage)
Observation of the landscape has been the focus of a great deal of renewed interest in recent years. Having taken into account the criticism directed at the “integrated perspective” adopted by Vidalian geographers, it has now become a heuristic way of understanding an environment considered as a socio-ecological territorial complex and of defining action in this domain. This article focuses on the renewed interest in landscape observation and on the practices associated with it through experiments conducted by the authors in different cultural, social and territorial contexts (the Garonne Valley and mountainous regions of Southern Europe, the Himalayas, and Reunion Island) and with different objectives in mind (research, teaching, action research). These experiments involve an inductive approach. The landscape has clearly been presented as a scaled surface, the methodical deciphering of which is adopted in addressing problems and conducting interventions. As conceived of by the authors, the observation/interpretation of the landscape is a part of a collective construct involving the knowledge, expertise, representations and practices of all the stakeholders involved, whether they are researchers, elected representatives, members of social and professional organisations, or inhabitants. It is founded on the assumption of the possible existence of reflexive observer-stakeholders capable of defining their actions in the full knowledge of their impacts on territorial and environmental processes. The objective is to create the conditions for a mediation of the landscape, making action possible in a complex and uncertain world and to adopt an innovative approach regarding sustainable development.